ANALYSIS OF FOOD LAWS IN INDIA WITH REFERENCE TO FOOD SAFETY AND STANDARDS AUTHORITY OF INDIA (International Journal of Food and Nutritional Sciences, 2022)
"Right to healthy food" is an fundamental concept included in Indian Constitution for ensuring a better quality of life for its citizens, and it can be effectively regulated by having a proper legal framework of food laws in India